Advances in Knowledge Regarding Arterial Curvature and its Relationship to Ischemic Stroke: A Narrative Review - Lin-Han Zhang; Fei Cao (Artery Research)
Abstract Curvature of large arteries in the cervical and intracranial regions represents a common morphological vascular alteration. However, the precise mechanisms underlying its formation and progression remain unclear. Increasing evidence suggests a potential correlation between arterial curvature and ischemic stroke. This manuscript involves a review of the relevant literature that delineates the measurement techniques for assessing arterial curvature, the mechanisms contributing to its formation, and recent evidence linking arterial curvature to stroke. Arterial curvature is primarily influenced by genetic factors, hypertension, sex, and age, and it may indicate weakened arterial walls. Furthermore, the haemodynamic changes associated with arterial curvature can result in reduced cerebral perfusion pressure, endothelial dysfunction, oxidative stress, and inflammatory responses. These factors contribute to the development of atherosclerosis and the formation of arterial dissections. The degree of arterial curvature may serve as a risk factor for cerebral ischemia, alongside traditional vascular risk factors. Further investigation into arterial curvature could yield valuable insights for clinicians managing patients with curved vessels.